Dysfunction in Motor Coordination in Neonatal White Matter Injury Model without Apparent Neuron Loss. Issue 7 (July 2016) - Misumi, Sachiyo; Ueda, Yoshitomo; Nishigaki, Ruriko; Suzuki, Mina; Ishida, Akimasa; Jung, Cha-Gyun; Hida, Hideki
We made a white matter injury (WMI) model with mild hindlimb dysfunction by right common carotid artery occlusion followed by 6% oxygen for 60 min at postnatal day 3 (P3), in which actively proliferating oligodendrocyte (OL) progenitors are mainly damaged. To know whether this model is appropriate for cell therapy using OL progenitors, the pathological response to mild hypoxia–ischemia (H-I) in neurons and OL lineage cells and myelination failure were investigated along with gene expression analysis. In WMI model rats, coordinated motor function, as assessed by the accelerating rotarod test, was impaired. The dysfunction was accompanied by myelination failure in layers I–IV of the sensorimotor cortex. Although several oligo2-positive OLs stained positive for active caspase 3 in the cortex and white matter at 24 h after H-I, few NeuN-positive neurons were apoptotic. Argyrophil-III staining for damaged neurons revealed no increase in the number of degenerating cells in the model. Moreover, the total number of NeuN-positive neurons in the cortex was comparable to that of controls 7 days later. Retrograde labeling of the corticospinal tract with Fluoro-Gold revealed no significant loss of layer V neurons. In addition, no decrease in the numbers of cortical projecting neurons and layers V–VI neurons in both motor and sensory areas was observed. Interestingly, the numbers of inhibitory GABAergic cells immunoreactive for parvalbumin, calretinin, or somatostatin were preserved in the P26 cortex. Gene expression analysis at P5 revealed 98 upregulated and 65 downregulated genes that may relate to cell survival, myelin loss, and differentiation of OLs. These data suggest that impaired motor coordination was not induced by neuron loss but, rather, myelination failure in layers I–IV. As OL lineage cells are mainly damaged, this WMI model might be useful for cell-based therapy by replacing OL progenitors.